Simvastatin inhibits protein isoprenylation in the brain. (4th August 2016) - Ostrowski, Stephen M.; Johnson, Kachael; Siefert, Matthew; Shank, Sam; Sironi, Luigi; Wolozin, Benjamin; Landreth, Gary E.; Ziady, Assem G.
Highlights: A direct approach that can measure simvastatin effects on prenylation is explored in vitro and in vivo . 2D gel electrophoretic shifts reflected simvastatin inhibition of prenylation of CaaX-motif-containing GTPases. Inhibition by simvastatin occurred at concentrations as low as 50 nM. Simvastatin inhibited RhoA, Cdc42, and H-Ras prenylation in rodent brains following oral administration of clinical doses. Abstract: Evidence suggests that 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors, or statins, may reduce the risk of Alzheimer's disease (AD). Statin action in patients with AD, as in those with heart disease, is likely to be at least partly independent of the effects of statins on cholesterol. Statins can alter cellular signaling and protein trafficking through inhibition of isoprenylation of Rho, Cdc42, and Rab family GTPases. The effects of statins on protein isoprenylation in vivo, particularly in the central nervous system, are poorly studied. We utilized two-dimensional gel electrophoresis approaches to directly monitor the levels of isoprenylated and non-isoprenylated forms of Rho and Rab family GTPases. We report that simvastatin significantly inhibits RhoA and Rab4, and Rab6 isoprenylation at doses as low as 50 nM in vitro . We also provide the first in vivo evidence that statins inhibit the isoprenylation of RhoA in the brains of rats and RhoA, Cdc42, and H-Ras in the brains of mice treated with clinically relevant doses of simvastatin.